2011
DOI: 10.1007/s10973-011-2064-x
|View full text |Cite
|
Sign up to set email alerts
|

Some aspects of thermal load and operating indexes after downsizing for internal combustion engine

Abstract: The twenty-first century started with many downsizing applications. This important trend in the engine technology has been constantly developed. There are questions about limits and on the other hand new solutions in the face of new materials, tribological discovery, lubrication oils, turbo-or supercharging, new control electronic system of the engine run, higher accuracy in designing, etc. Some of parameters of thermodynamics of working cycle and thermal load according to the downsizing engine parameters were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 8 publications
0
15
0
2
Order By: Relevance
“…Supercha-rger BP Type of engine [10] Roots blower-type super-charger 100,120,140 kPa (abs) 1 cylinder, CR: 18, 5.1 kW /2400rpm, IP:21.7 MPa [11] Two stage reciprocating air compressor 20,30, 40 kPa (g)) 1 cylinder, 3.7 kW at 1500 rpm, CR: 16.5 [12] two-stage reciprocating compressor 50 kPa(g) 1 cylinder, 3.7 kW at 1500 rpm, CR: 16.5, IP: 18, 21, and 24 MPa [13] two-stage reciprocating compressor 2,2.5, 3 bar (abs) 1 cylinder, 6 HP at 660 rpm, CR: 16.1,…”
Section: Refmentioning
confidence: 99%
See 1 more Smart Citation
“…Supercha-rger BP Type of engine [10] Roots blower-type super-charger 100,120,140 kPa (abs) 1 cylinder, CR: 18, 5.1 kW /2400rpm, IP:21.7 MPa [11] Two stage reciprocating air compressor 20,30, 40 kPa (g)) 1 cylinder, 3.7 kW at 1500 rpm, CR: 16.5 [12] two-stage reciprocating compressor 50 kPa(g) 1 cylinder, 3.7 kW at 1500 rpm, CR: 16.5, IP: 18, 21, and 24 MPa [13] two-stage reciprocating compressor 2,2.5, 3 bar (abs) 1 cylinder, 6 HP at 660 rpm, CR: 16.1,…”
Section: Refmentioning
confidence: 99%
“…The researchers have studied the influence of both supercharging as well as the variable compression ratio separately on performance characteristics of a diesel engine. The supercharging and charge cooling have improved the peak pressure, charging ratio, and brake mean effective pressure by 18 %, 5 %, and 53 % respectively [11]. It is reported that for all tested fuels, the emission of CO and smoke has scaled down considerably and brake thermal efficiency improved notably [12].…”
Section: Introductionmentioning
confidence: 99%
“…There are many considerations, however, for the valve seat and valve to have good performance as a pair, the following characteristics must be considered: high temperature resistance; wear resistance; corrosion resistance; tenacity; impact resistance and thermal conductivity [7].…”
Section: Introductionmentioning
confidence: 99%
“…While different possibilities may allow to achieve these goals [2], manufacturers are specially interested in engine downsizing. However, among other problems a serious issue associated with this technical solution is heat transfer, since the implied increase in the relative heat losses, together with the observed changes in their spatial distribution [3] actually pose intrinsic limitations to the engine size limits [4]. Additionally, the potential benefits of the use of suitable thermal management strategies is well established [5,6].…”
Section: Introductionmentioning
confidence: 99%